Challenges in English Writing within Blended Learning Environment - Lilia Indriani; Widya Ratna Kusumaningrum; Rolisda Yosintha (IAIN Syekh Nurjati Cirebon, 2021)
This study reports a case study research in Writing Blended Learning Environment for higher education that enriched digital environment study especially in the pandemic of Covid-19. It examines the students’ writing apprehension and their performance as perceived by a selected group of EFL students who enroll in Professional Writing class. Questionnaires were administered to three writing lecturers and fifty students of the English Department, Universitas Tidar. The obtained data were analyzed quantitatively using descriptive statistics, while those obtained from the interview were analyzed qualitatively using Miles, Huberman, and Saldana’s model (2014). The findings show that there are many challenges faced by both the teachers and the students when they implemented this writing blended learning environment. Though, some challenges give not only the pitfalls but also positive contribution to the students’ learning progress in their writing. The study found that students need specific and intensive instruction, practice, and feedback for improving their writing skills. It is also found that learning writing through writing blended learning environment is somehow interesting and also challenging in some covered topics and activities, while lecturers still have their instructional and pedagogical roles in a blended learning environment.